1992
DOI: 10.1016/s0022-5347(17)37555-9
|View full text |Cite
|
Sign up to set email alerts
|

Renal Scarring Following Reflux and Nonreflux Pyelonephritis in Children: Evaluation with 99m Technetium-Dimercaptosuccinic Acid Scintigraphy

Abstract: 99mTechnetium dimercaptosuccinic acid (DMSA) scintigraphy is the imaging modality of choice for the detection of acute pyelonephritis and chronic renal scarring in children. Using the DMSA scan we prospectively evaluated renal scarring after reflux and nonreflux pyelonephritis in children. The study population consisted of 33 patients with acute pyelonephritis documented by a DMSA renal scan at infection. The children were evaluated for renal scarring with a followup DMSA scan 4 to 42 months (mean 10.7 months)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
122
2
26

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(160 citation statements)
references
References 33 publications
10
122
2
26
Order By: Relevance
“…Recent reports have challenged the assumption that APN in children is usually associated with VUR. 4,11,12 Our study has supported this view; 55% of children with DMSA-documented changes of APN had no VUR. APN in the absence of VUR has been attributed to bacterial virulence, e.g., the presence of P. fimbriae in certain strains of Escherichia coli allowing ascending infection, 4 or due to hematological spread.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Recent reports have challenged the assumption that APN in children is usually associated with VUR. 4,11,12 Our study has supported this view; 55% of children with DMSA-documented changes of APN had no VUR. APN in the absence of VUR has been attributed to bacterial virulence, e.g., the presence of P. fimbriae in certain strains of Escherichia coli allowing ascending infection, 4 or due to hematological spread.…”
Section: Discussionsupporting
confidence: 68%
“…7 Both US and IVU underestimate the degree of renal parenchymal involvement, with a high rate of false-negative results. [5][6][7][8]11 Fifty-eight of our children studied with DMSA scans showed evidence of APN. This is comparable to 66% reported by others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em crianças com pielonefrite, observou-se semelhante proporção da presença de E. coli entre as que desenvolveram e as que não desenvolveram cicatrizes renais 30 , semelhante ao que ocorreu neste trabalho. Tem-se questionado o risco da maior formação de cicatrizes em pacientes com infecção pela E. coli P fimbriada 7,25,30 .…”
Section: Discussionunclassified
“…The majority of studies demonstrated that the risk of renal scarring decreases with age and is highest in children in the first year of life (Hansson et al, 1999;Vernon et al, 1997;Arant, 1991;Benador et al, 1997;Smellie et al,1998;Sheu et al, 2009). This may be related to the correction of anatomical and/or functional urinary system abnormalities and the decrease in susceptibility of renal parenchyma to infection due to defense mechanisms maturation (Benador et al, 1997;Rushton et al,1992). Dissimilar results were obtained by Pecile et al (2009).…”
Section: Introductionmentioning
confidence: 99%